Blockchain-Enabled Digital Payment Systems and Their Impact on Financial Inclusion: A Computational Economic Analysis Review - Ermaini; A Arniwita; Rahmi Handayani (PT ARRUS Intelektual Indonesia, 2026)
Digital payment methods have changed and prospects for financial inclusion have increased due to the quick advancement of financial technology. However, obstacles like high transaction costs, inadequate financial infrastructure, and dependence on centralized middlemen continue to plague many emerging nations. Blockchain technology provides a secure, decentralized payment system that can increase transaction accessibility and efficiency. This study uses a computational economic approach to investigate how blockchain-enabled digital payment systems affect financial inclusion. The study uses machine learning models, such as Random Forest, Gradient Boosting, Support Vector Machine, and Neural Networks, to examine the connection between financial inclusion metrics, digital payment efficiency, and blockchain adoption. The findings demonstrate that blockchain-based payment systems greatly enhance transaction efficiency, lower transaction costs, and boost the use of digital payments. Higher levels of financial inclusion and accessibility are a result of these advancements. The results show how crucial blockchain infrastructure is to fostering inclusive digital financial ecosystems and offer policy recommendations for developing nations looking to improve their digital financial inclusion initiatives.